IMPROVING THE STUDENTS’ ABILITY IN ENGLISH GRAMMAR THROUGH “ EASY TO LEARN ENGLISH GRAMMAR COMPACT DISC” COMPUTER SOFTWARE - Wildhan Burhanuddin (Universitas Muhammadiyah Makassar, 2015)
This study aims at knowing the students’ interest in learning English Grammar through Easy to Leam English Grammar Compact Disc (ELEG CD) computer software. This research used the descriptive method with twenty-eight participants from the students of TKJ (Technique, Computer, and Network) in the SMK Bajiminasa Makassar. The researcher collected data through a questionnaire that aims at knowing students’ ability in learning English Grammar through Easy to Learn English Grammar Compact Disc (ELEG CD) computer software. The researcher itemized five positive statements and five negative statements. The writer also conducted observation as additional information about the condition of computer laboratory, “Easy to Learn English Grammar Compact Disc” computer software and the students’ behaviors in playing it, It aims to know how computer laboratory and Easy to Learn English Grammar Compact Disc computer software influence students in learning English especially English grammar. The result of this research showed that the students of TKJ (Technique, Computer, and Network) in the SMK Bajiminasa Makassar were increasing in learning English Grammar through Easy to Learn EnglishGrammar Compact Disc computer software. This was proved by the aggregate percentage of the students got from the questionnaires that is from item l up to 10. Based on the findings, the researcher makes the conclusion that in English grammar through “ Easy to Learn English Grammar Compact Disc” computer software could improve the students’ ability.